2021
DOI: 10.1002/uog.23619
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and neonatal outcomes of COVID‐19: coreporting of common outcomes from PAN‐COVID and AAP‐SONPM registries

Abstract: What are the novel findings of this work? Preterm delivery occurred in a higher proportion of women with SARS-CoV-2 infection in the PAN-COVID and AAP-SONPM registries compared to contemporaneous and historical national data from uninfected women in the UK and USA. The majority of preterm deliveries occurred between 32 + 0 and 36 + 6 weeks' gestation. SARS-CoV-2 infection in pregnancy did not appear to be associated with a clinically significant effect on fetal growth, adverse neonatal outcome or the rate of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(125 citation statements)
references
References 22 publications
9
112
1
3
Order By: Relevance
“…is not yet known, given the relative rarity of placental infection and in utero transmission of SARS-CoV-2 and lack of reported sex disaggregated data in these areas [2][3][4]. Reporting the sex differences described here represents the first essential step toward a more nuanced understanding of how fetal sex may influence vulnerability or resilience to placental and fetal infection with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…is not yet known, given the relative rarity of placental infection and in utero transmission of SARS-CoV-2 and lack of reported sex disaggregated data in these areas [2][3][4]. Reporting the sex differences described here represents the first essential step toward a more nuanced understanding of how fetal sex may influence vulnerability or resilience to placental and fetal infection with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 91%
“…More than 82,000 pregnant women in the United States have tested positive for SARS-CoV-2 [1], with numbers rising daily. Reported rates of vertical transmission of SARS-CoV-2the passage of SARS-CoV-2 from mother to baby during pregnancy or childbirthrange from 1-3% [2][3][4]. Case reports and case series documenting placental SARS-CoV-2 infection in the second and third trimesters suggest that SARS-CoV-2 infection of the placenta may be an intermediate step in vertical transmission [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women with COVID-19 had higher rates of preterm delivery than did those without the disease, according to data from two registries that tracked more than 4,000 women with confirmed or suspected COVID-19 in the United States and the United Kingdom 6 . Twelve per cent of participants in the UK registry delivered before 37 weeks, compared with the rate for 2020 of 7.5% across England and Wales; in the United States, 15.7% of women with COVID-19 experienced preterm birth (the expected national rate is 10%).…”
Section: Prenatal Risksmentioning
confidence: 99%
“…Only those women with specific chronic diseases should be considered on a case-by-case basis [35,36]. The most recent data presented by Mullins et al, based on a group of 4,005 pregnant women with either suspected or confirmed SARS-CoV-2 infection, has indicated the need for enhanced precautions to prevent SARS-CoV-2 infection in pregnancy, particularly in the context of the increased risks of preterm delivery and maternal mortality, and the need for priority vaccination of women planning pregnancy [37].…”
Section: Vaccination In Pregnant Womenmentioning
confidence: 99%